A study on prescribing errors in in-patients of a corporate tertiary care hospital in North India - Yadav, Ashish; Rashed, Mohammed R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Prescribing errors are a subset of medication errors which have a potential for grave harm to the patient. Identification and acknowledgement of such errors can ameliorate much of this danger. Studies of prescribing errors are sparse in India. Such studies, whatever have been conducted, mainly focus on the out-patients or the patients on discharge. Hence, this study was undertaken to study the prescribing errors in prescriptions generated for patients admitted in wards of a corporate hospital in North India. Methods: The prescriptions for in-patients admitted in wards were analyzed for different types of prescribing errors in individual drug orders and prescription as a whole. Results: The prescribing error rate was found to be 3.3% in this study. Of all errors, errors leading to delays in patient care (i.e. Errors of prescription writing) (54.54%) and erroneous copying of the prescription to the drug chart by junior/ resident doctors (Transcription errors) (31.31%) were found to be the major causes of prescribing errors in this study. Of the former category, prescribing a wrong strength (24.24%) and illegible drug orders (12.12%) were the most numerous error subtypes. Errors leading to sub-optimal patient care (i.e. Errors of decision making) were least identified of which Therapeutic duplication (12.12%) was the most common subtype. Conclusions: The error rate found in this study is comparable to the data available from developed countries. However, there are significant differences in the occurrences of error subtypes found in this study as compared to the studies of the west.